36. Isolated monophasyc whyte matter lesion: Neoplasm or tumefactive MS?. Issue 1 (January 2015) - Stipa, G.; Frondizi, D.; Moschini, E.; Di Schino, C.; Galletti, F.; Principi, M.; Aprile, I.; Conti, C.; Rossi, V.; Fattori, P.; Mancini, A.; Roscini, N.; et al.
<x xml:space="preserve">Abstract</x> Isolated monophasyc whyte matter lesion could have a demyelinating or neoplastic origin. A 26 years old woman, at the 6th week of pregnancy, acutely presented motor deficit to the right side, and aphasia. MRI showed a left temporal lesion in the subcortical white matter, without edema, and with dishomogeneous enhancement. Spectroscopic MR pointed out a choline increase, and a reduction of NAA peak. Visual evoked potential showed peculiar cortical response, while liquoral exam showed oligoclonal bands. Steroid treatment produced a substantial clinical and radiological stability. After miscarriage, the patient underwent brain biopsy, which in this case was the gold standard for diagnosis.